Fatigue: assess and address it - Tanja A. Kuut; Hans Knoop; Hedy A. van Oers; Lotte Haverman (Journal of Patient-Reported Outcomes, 2026)
Abstract Severe fatigue is highly prevalent in patients across different medical conditions and can only be partially explained by disease-specific factors. Also, fatigue is often seen by patients as one of the most disabling symptoms. Despite its substantial impact, fatigue is often not systematically discussed in clinical practice. Effective generic treatments exist for patients with severe fatigue. When fatigue is not assessed, patients may be withhold the opportunity to get advice on how to manage fatigue or receive effective interventions to achieve meaningful improvement. Therefore, designated health care professionals involved in patient care should be able to recognize and address fatigue as a key patient-reported outcome.